ESTABLISHMENT OF SOFTWARE QUALITY ASSURANCE SYSTEM FOR SMALL SOFTWARE CUSTOMIZATION PROJECTS IN INFORLINK SYSTEMS SDN BHD - Mohammadmahdi Sadrnejad, 1983-, author; Salwani Mohd. Daud, Assoc.Prof.Dr., supervisor; Sekolah Informatiks Termaju (Kuala Lumpur : Universiti Teknologi Malaysia, 2013)
Thesis